Testing the effectiveness of a dating violence prevention program among college students in Istanbul - Üstünel, Anıl Özge. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Dating violence among college students is a psychological and social issue associated with serious academic, psychological and physical health risks. In Turkey, there has been no published work on any systematic effort or program for the prevention of dating violence in college samples. The present study aimed to fill this gap by implementing a dating violence prevention program to college students attending a university in Istanbul and employed a mixed-methods approach to evaluate its effectiveness. A program was designed to promote equality, safety, mutuality and responsibility in dating relationships, informed by feminist clinical approaches. The program was pilot tested and implemented to five groups (47 participants) in eight weekly consecutive sessions between February-May 2017. In the quantitative part, a quasi-experimental pretest-posttest design with a control group (49 participants) was used to explore the program’s effect on behavioral and attitudinal outcome measures. A series of ANCOVAs on posttest scores whilst controlling for pretest scores and relevant covariates showed no improvement in emotion approach coping, accommodative behavior, benevolent attitudes towards women, ambivalent attitudes towards men and attitudes towards psychological dating violence. The significant changes obtained in hostile attitudes towards women and in attitudes towards physical dating violence were promising. In the qualitative part, semi-structured individual interviews were conducted with the prevention groups to explore the processes which facilitated and hindered change. A constructivist grounded theory approach was used. The present results showed that feminist clinical perspectives with skills-based components can provide a valuable guiding framework for future dating violence prevention efforts.
Keywords: Flirting.; Dating violence -- Istanbul.